Post-traumatic Growth pada Wanita Dewasa Awal Pasca Perceraian Orang - Awaluddin, Andi Sopy; Widyastuti; Zainuddin, Kurniati (Mediapsi, 2024)
Parental divorce is a traumatic event that has negative impact but can be an opportunity for positive growth. This study aims to determine description of post-traumatic growth in women after parental divorce and its factors. This study used a phenomenological qualitative method with interpretive phenomenological analysis (IPA) involving three participants who had negative impacts but then showed positive growth. The results showed that there were seven growths: development of religiosity, new possibilities, changes in priorities, appreciation of life, increased meaningful relationships, personal strength, in addition, wise mindset which is a new finding. Based on the results of data analysis shows that there are seven growth factors: social support, spirituality, optimism, age, resilience, in addition, pressure, motivation which are two new findings. The results can encouraging children to grow by accepting and taking positive things from parental divorce and reminding the importance many factors can help them to reach post-traumatic growth.